2014
DOI: 10.1074/jbc.m114.593012
|View full text |Cite|
|
Sign up to set email alerts
|

Phospholipid Flippase Activities and Substrate Specificities of Human Type IV P-type ATPases Localized to the Plasma Membrane

Abstract: Background:The enzymatic activities of mammalian P4-ATPases are incompletely characterized. Results: ATP11A and ATP11C catalyze flipping of NBD-PS and NBD-PE, whereas ATP8B1 preferentially catalyzes flipping of NBD-PC. Furthermore, some PFIC1 mutants of ATP8B1 failed to flip PC. Conclusion: ATP11A/ATP11C and ATP8B1/ATP8B2 preferentially translocate aminophospholipids and PC, respectively. Significance: This is the first evidence showing that the PC-flipping activity of ATP8B1 is associated with the episode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(188 citation statements)
references
References 49 publications
6
165
1
Order By: Relevance
“…These results suggest that PC in the outer and inner leaflet do not coordinate across the bilayer in caveolae. Recently it has been reported that type IV P-type ATPase ATP8B1/ATP8B2 preferentially translocates PC from the outer to the inner leaflet of the plasma membrane (Takatsu et al, 2014). Our results suggest that caveolae are the site of the transbilayer movement of PC in HSFs.…”
Section: Research Articlesupporting
confidence: 54%
“…These results suggest that PC in the outer and inner leaflet do not coordinate across the bilayer in caveolae. Recently it has been reported that type IV P-type ATPase ATP8B1/ATP8B2 preferentially translocates PC from the outer to the inner leaflet of the plasma membrane (Takatsu et al, 2014). Our results suggest that caveolae are the site of the transbilayer movement of PC in HSFs.…”
Section: Research Articlesupporting
confidence: 54%
“…Eukaryotic cells, from mammals to yeast, contain ATPfueled flippases that translocate PE and PC from the exo plasmic to the cytosolic leaflet of late secretory organelles (33)(34)(35)(36). These activities may influence SMSmediated SM and CPE production by limiting the amount of PC and PE available for consumption by SMS enzymes.…”
Section: Functional Analysis Of Sms Enzymes In Defined Lipid Environmmentioning
confidence: 99%
“…Association with CDC50 proteins is crucial to the stability, subcellular localization and flippase activity of P4-ATPases [23,24,28,33,35], but the available evidence does not indicate a role for CDC50 proteins in determination of substrate specificity [38,[41][42][43]. The interaction between yeast flippase Drs2 and its specific partner Cdc50p was shown to fluctuate during the transport cycle, with the strongest association occurring in the E 2 P conformation, in which the P4-ATPase binds its phospholipid substrate from the exoplasmic membrane leaflet [22,24].…”
Section: Discussionmentioning
confidence: 99%